1999
DOI: 10.1016/s0378-1097(99)00246-3
|View full text |Cite
|
Sign up to set email alerts
|

An immunomagnetic separation polymerase chain reaction assay for rapid and ultra-sensitive detection of Cryptosporidium parvum in drinking water

Abstract: A sensitive and rapid method was developed to detect Cryptosporidium parvum oocysts in drinking water. This molecular assay combined immunomagnetic separation with polymerase chain reaction amplification to detect very low levels of C. parvum oocysts. Magnetic beads coated with anti-cryptosporidium were used to capture oocysts directly from drinking water membrane filter concentrates, at the same time removing polymerase chain reaction inhibitory substances. The DNA was then extracted by the freeze-boil Chelex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…PCR was described as more rapid, sensitive, and specific for Cryptosporidium species detection in environmental water samples (17,19,21); the sensitivity was found to be comparable for TaqMan PCR and conventional IFA (7). For DNA extraction, Sluter et al (38) showed that three cycles of freezing-thawing were sufficient to expose Cryptosporidium oocyst DNA, resulting in higher sensitivity than proteinase K digestion or sonication.…”
Section: Discussionmentioning
confidence: 99%
“…PCR was described as more rapid, sensitive, and specific for Cryptosporidium species detection in environmental water samples (17,19,21); the sensitivity was found to be comparable for TaqMan PCR and conventional IFA (7). For DNA extraction, Sluter et al (38) showed that three cycles of freezing-thawing were sufficient to expose Cryptosporidium oocyst DNA, resulting in higher sensitivity than proteinase K digestion or sonication.…”
Section: Discussionmentioning
confidence: 99%
“…This has greatly reduced the sensitivity of PCR detection of oocysts in various water samples. The PCR inhibitors can be removed by IMS (8,9). This practice led to successful detection of Cryptosporidium oocysts in water samples from the 1993 outbreak in Milwaukee, Wis., by a Cryptosporidium genus-specific PCR technique (9) and to genotyping of C. parvum parasites in surface and filter backwash water samples by an integrated cell culture-PCR technique (3).…”
Section: Discussionmentioning
confidence: 99%
“…4). Although we do not routinely run controls for PCR inhibitors, they should be sufficiently removed during filtration and IMS (13,16,30). Third, low numbers of oocysts in the environment may go undetected by IFA due to sample dilution and competition of sample debris with fluorescent antibodies.…”
Section: Discussionmentioning
confidence: 99%